FEATURES OF EVALUATING THE EFFICIENCY AND DEVELOPMENT OF MEDICAL ORGANIZATIONS - TIURINA, Nila; ANTONYUK, Vasyl (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the study, the concepts of "effect", "efficiency" and "effectiveness" are defined and distinguished, possible directions and components of achieving results are defined. The essential characteristics of the concept of efficiency in the field of health care have been clarified. It is substantiated that the main priority directions of the analysis of the activity of a medical organization are the assessment of the level of achievement of medical, social and economic efficiency, the detailed content of these concepts. Indicators and criteria for the effectiveness of medical institutions, basic principles of economic efficiency evaluation, and their content have been formed. The main features of evaluating the effectiveness and development of the activity of a medical organization are highlighted. The need to increase the efficiency of management of health care facilities under modern conditions has been updated. A structural scheme for improving the efficiency and development management mechanisms of the medical organization was developed. The priority directions for improving the efficiency of health care facility management have been determined. It was established that the strategic activity of a medical institution can be presented in the form of four main perspectives: finances, personnel, patients, and internal processes. A structural diagram of the strategic activity of the medical institution within the framework of the system of balanced indicators has been developed.
Keywords: efficiency; effectiveness; effectiveness of medical facilities; mechanisms of efficiency management